The Effect of Psychosocial and Neuropsychiatric Factors on Medication Adherence in a Cohort of Women With Systemic Lupus Erythematosus. Issue 8 (December 2016) - Flower, Cindy; Hambleton, Ian; Campbell, Mike
Abstract : Background: Medication adherence in systemic lupus erythematosus (SLE) reduces disease activity and the risk of flares. Objectives: We evaluated adherence in women with SLE who exhibit high morbidity and mortality. We evaluated demographic data and 2 conventional adherence predictors: self-efficacy and health literacy, along with 2 potential neuropsychiatric SLE complications: cognitive dysfunction and depression. Methods: One hundred six women randomly selected from the Barbados National Lupus Registry completed the Self-efficacy for Appropriate Medication Use Scale, Rapid Estimate of Adult Literacy in Medicine–Short Form, Cognitive Symptom Inventory, Beck Depression Inventory II, and Morisky's Medication Adherence Questionnaire (MAQ). This study explored the effects of psychosocial and neuropsychiatric functioning on adherence using ordinal logistic regression. Results: Sixty percent reported high MAQ scores. The probability of high MAQ scores was lower among younger patients ( P = 0.001) and those with shorter disease duration ( P = 0.05). The probability of high MAQ scores fell with lower perceived self-efficacy (odds ratio [OR], 0.80; 95% confidence interval [CI], 0.73–0.89; P < 0.001), worsening cognitive function (OR, 0.90; 95% CI, 0.84–0.97; P = 0.004), and increasing depression (OR, 0.93; 95% CI, 0.88–0.97; P = 0.002). There was no strong relationship between MAQ score and health literacy (OR, 0.37; 95% CI, 0.13–1.03; P = 0.06). Conclusion: Women with SLE who are younger and those with shorter disease duration should be assessed for medication adherence. Screening at diagnosis followed by routine assessment of cognitive dysfunction and depression along with perceived self-efficacy may further identify the most vulnerable subgroup who should be targeted with personalized intervention strategies.